Literasi Finansial Dan Penghindaran Gharar Dalam Pengelolaan Keuangan Mahasiswa - Sauqi Akbar Mubarok; Jenuri Jenuri; Asep Rudi Nurjaman (VALUE, 2024)
Abstract This research aims to analyze how CGN Putra boarding students manage finances to manage and also use the money they have to avoid Gharar. The location of the research was conducted at CGN Putra Kost located on Jalan Pandanwangi No. 37 Cibiru Wetan, Cileunyi District. This research was conducted on male students of Universitas Pendidikan Indonesia who lived in CGN Putra boarding house with a total of 7 students. This research is expected to be able to provide ideas about financial literacy and can improve personal financial management skills, especially for students. The CGN male boarding students agreed that financial management is very important. There are some of them who record income and expenditure, however, most of them do not record income and expenditure. CGN boarding school students can manage finances well and save when there are funds left. However, there are some students who have not been able to manage finances properly, this can be overcome by providing knowledge on the importance of financial management for students, especially boarding children to avoid Gharar's behavior